2003
DOI: 10.2337/diacare.26.10.2829
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Active Family Nutritional Support in Navajos’ Type 2 Diabetes Metabolic Control

Abstract: OBJECTIVE -We examined if active family nutritional support is associated with improved metabolic outcomes for Diné (Navajo) individuals living with type 2 diabetes.RESEARCH DESIGN AND METHODS -The presence of family support, using variables identified in earlier ethnographic research, was assessed via surveys in a convenience sample of 163 diabetic individuals. Diabetes outcome measures (HbA 1c , serum glucose, triglycerides, total cholesterol, creatinine, and systolic and diastolic blood pressure measures) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 29 publications
3
45
0
2
Order By: Relevance
“…Sample sizes ranged from 15 to 3,535 participants. In both designs, more studies suggested that higher levels of social support were associated with improved diabetes-related clinical outcomes (HbA1c, BP, lipids) [17, 22, 24, 26, 28••, 29•, 30, 33, 34, 35••, 36••, 37, 38]. This association held true regardless of the avenue for social support exchange or delivery (i.e., peer support, couples/spouse, and nurse manager) [22, 23, 34, 35••, 36••, 37, 38].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sample sizes ranged from 15 to 3,535 participants. In both designs, more studies suggested that higher levels of social support were associated with improved diabetes-related clinical outcomes (HbA1c, BP, lipids) [17, 22, 24, 26, 28••, 29•, 30, 33, 34, 35••, 36••, 37, 38]. This association held true regardless of the avenue for social support exchange or delivery (i.e., peer support, couples/spouse, and nurse manager) [22, 23, 34, 35••, 36••, 37, 38].…”
Section: Resultsmentioning
confidence: 99%
“…Both of these behavioral-targeted support mechanisms improved clinical outcomes in diabetes management [24, 30, 33]. Furthermore, Epple and colleagues demonstrated that diet-related clinical outcomes (low-density lipoprotein [LDL], total cholesterol, triglycerides [TG], and HbA1c) were best when “other family members” (not the patient with T2DM) cooked the meals [33]. It should be mentioned as well that these “best outcomes” were observed in female participants [33].…”
Section: Resultsmentioning
confidence: 99%
“…Little is known regarding the influence of social support and T2DM-related outcomes or behaviors among American Indians. An examination with Navajos with T2DM found that when the majority of the meals were cooked by family members for someone with T2DM, they were more likely to have lower HbA1c levels (Epple, Wright, Joish, & Bauer, 2003). A more recent qualitative study with American Indians and Alaska Natives with T2DM found that social support emerged as an important aspect in their T2DM management.…”
Section: Discussionmentioning
confidence: 99%
“…Studies like the Strong Heart Study [46], the Zuni Kidney Project [79], and the Cherokee Diabetes Study [10] focus on AI/AN and use biological sampling with full permission from participants to collect samples for research purposes. However, it is common for studies to extract data from medical records or previously collected samples [11]. …”
Section: Introductionmentioning
confidence: 99%